The impact of sex change on status matters - حسين, عادل ناصر (Journal of Legal Sciences, 2020)
When a person responds to the temptation of Satan and changes his sex from male to female or vice versa, it will be terrible, He is neither male nor female; Because this change will be apparent only and will not affect the person,This change if it occurs has implications impaction Bor personal status issues.